Upconversion luminescence and Visible-Infrared Properties of β-NaLuF4:Er3+ Microcrystals Synthesized by the Surfactant-Assisted Hydrothermal Method. (18th June 2014) - Lin, Han; Yan, Xiaohong; Zheng, Jin; Dai, Changjie; Chen, Yuan
Abstract : We report the obtention of β -NaLuF4 microcrystals doped with Er 3+ ions by the surfactant-assisted hydrothermal method. It was found that shape modulation could be realized by changing the surfactants (ethylenediaminetetraacetic acid, polyvinylpyrrolidone, and trisodium citrate) introduced into the reaction system. The surfactants can strongly control the size and shape of as-prepared samples through absorbing on the surface of primary particles and/or coordinating with rare earth ions. Hexagonal prism-like β -NaLuF4 :Er 3+ microcrystals demonstrate intense upconverted luminescence (UCL) pumped by 1.54 μ m infrared laser in comparison with hexagonal tube-like, disk-like, and sphere-like microcrystals, which exhibit great distinction. More interestingly, a synergistic effect combined dual mode (i.e., downconversion and upconversion) with 8% absolute enhancement rate of the red emission centered at 659 nm ( 4 F9/2 → 4 I15/2 ) is witnessed in hexagonal prisms β -NaLuF4 :Er 3+ phosphors by employing the dual wavelength 416 nm and 1.54 μ m excitation source for the first time.